The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/polp.12436
|View full text |Cite
|
Sign up to set email alerts
|

Global Korea Scholarship students: Intention to stay in the host country to work or study after graduation

Abstract: Over the past few decades, South Korea has increasingly sought to attract international talent. Every year, hundreds of students are invited to study in the country on a competitive scholarship provided by the government. Upon graduation, students are equipped with a tertiary degree, as well as knowledge of the Korean language and culture. This study examines the determinants of intention to stay in South Korea to work or study after graduation, using a 2019 survey of Global Korea Scholarship recipients (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 105 publications
1
12
0
Order By: Relevance
“…Some prior studies attempted to examine the attractive factors (such as economic, institutional and environmental) that impact students' decisions to study abroad and, possibly, to remain in the host country once their studies are finished. For example, Istad et al (2021) discovered that the students' intentions to do so are positively correlated with their satisfaction with their academic performance, social adjustment and quality of life in South Korea. Mazzarol and Soutar (2002) evaluated prospective students from four different countries (Indonesia, Chinese Taiwan, India and Mainland China) using the push-pull factor theory to explain why some students choose to study abroad or opt to stay in the host country.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Some prior studies attempted to examine the attractive factors (such as economic, institutional and environmental) that impact students' decisions to study abroad and, possibly, to remain in the host country once their studies are finished. For example, Istad et al (2021) discovered that the students' intentions to do so are positively correlated with their satisfaction with their academic performance, social adjustment and quality of life in South Korea. Mazzarol and Soutar (2002) evaluated prospective students from four different countries (Indonesia, Chinese Taiwan, India and Mainland China) using the push-pull factor theory to explain why some students choose to study abroad or opt to stay in the host country.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Since international students obtain knowledge and develop skills during their studies in the host countries, international graduates are viewed as a short cut to boosting the number of skilled talents in the country where they studied and graduated (Farivar et al, 2019). However, several countries experiencing a shortage of skilled workers have also observed that numerous international graduates depart from the host country after completing their education for various reasons (Han et al, 2015;Istad et al, 2021) and they either go back home or seek job opportunities elsewhere (Li and Bray, 2007). This has led to a brain drain in the host countries (mostly developed nations) (Docquier and Rapoport, 2012;Han et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al (2021) also find similar findings in the case of GKS students. On the other hand, Istad et al’s (2021) study show that GKS students’ home country’s level of development is not a significant determinant of their intention to stay in the country after graduation.…”
Section: Discussionmentioning
confidence: 65%
“…U-curve theory predicts that sojourners have an initial honeymoon period, followed by negative attitudes due to cultural maladjustment, and in the next stage a gradual adaptation and acculturation that would help them recover their initial favorable attitudes toward the host country (Black and O’Bright, 2016; Chien, 2016; Oberg, 1960; Stangor et al, 1996). In addition, previous literature finds that cultural dissimilarity (Alemu and Cordier, 2017; Jiang et al, 2020), perceived discrimination (Gesing and Glass, 2019; Jon, 2012; Sam, 2001; Tam and Ayhan, 2021; Yun and Vibber, 2012), discrepancy between expectations and experiences (Yun, 2015), lack of social interactions with host country nationals (Istad et al, 2021; Pedersen et al, 2011), and perceived academic satisfaction (Istad et al, 2021; Shafaei and Razak, 2016) may potentially lead to international students’ negative attitudes and/or behavior toward the host country.…”
Section: Scholarships As Public Diplomacymentioning
confidence: 99%